Effective use of assessment data to improve teaching and learning in primary schools in South Africa: four case studies South of Johannesburg - Botha, Elizabeth Mathakga (My University, 2015)
This research is an exploratory study of how data is used to promote teaching practice that improves learner achievement. Assessment data has been used to engage educators in an ongoing exploration of questions, with the intention to understand learner development. The international and Annual National Assessment benchmark tests to assess numeracy and literacy competence indicated poor learner performance in most South African schools, compared to learners in neighbouring countries and globally. Poor performance in South African schools is a challenge perceived as and related to a lack of effective school leadership. Research shows that effective leadership use of data for decision making is likely to facilitate change that promotes an effective culture of teaching and learning. Research also shows that use of data is effective when school leadership and teachers’ decisions are based on assessments of learners. There is evidence of improved learner performance where school leaders encouraged the use of assessment data for decision making to promote teaching; more so than where this was not the case. This study used grounded theory to understand variations of the phenomenon of the use of assessment data and the role of school leadership to improve teaching and learning. It employed an intensive, qualitative, interpretative methodology, which included a constructivist perspective. This allowed for greater insight into educators’ use of data for decision making. Case study methodology was used to collect and analyse data from school management teams and teacher focus groups for Maths and Languages. The data analysis from which the study drew includes specific coding and categorising of themes and patterns of data to ensure reliability. The research findings present evidence for the possible successful use of assessment data to improve teaching practice and learner performance. The data obtained from school management teams and teacher focus groups of one of the four case studies presented here, reveals a positive impact data-inquiry, and that through use of data, collaboration for decision making can provide opportunities for a successful teaching and learning culture. Continuous collaboration among teachers also provides for the creation of professional learning communities. A conceptual framework has been developed from the findings of this study. The ‘evidence-informed inquiry and action processes’ conceptualisation of the findings demonstrates how, through use of data, schools can interactively reflect, collaborate, and develop into professional learning communities to promote academic support and improve effective teaching and learning.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg in fulfilment of the requirements of the degree of Doctor of Philosophy. Johannesburg